Conservation vs. Development: A Case Study from Gangotri National Park, India - Rautela, Vipra; Dasgupta, Sabyasach; Todaria, N. P. (Indian Forester, 2019)
The study was carried out around Gangotri National Park (GNP), India, to assess the impact of conservation policies on natural resource extraction from GNP. Different conservation policies within legal framework were analysed for identifying conflict zones and generate people's perception towards conservation policies. Local people have been banned from extracting any benefit from the park while tourists are allowed to use even the core zone. This has created a feeling of discrimination in the local community against the national park. Few people were of the opinion that with the creation of national park and development of tourism, the environment of the region has deteriorated. Very few people had knowledge about forest policies. Contact with each other has been found to be the most effective method that can be used in the study region for disseminating information related to policies. There is a need for developing policies and management actions that serve the economic interests of the local people together with achievement of environment conservation goal. This is essential to generate public support.